Molecular signatures of beef tenderness: Underlying mechanisms based on integromics of protein biomarkers from multi-platform proteomics studies. (February 2021) - Gagaoua, Mohammed; Terlouw, E.M. Claudia; Mullen, Anne Maria; Franco, Daniel; Warner, Robyn D.; Lorenzo, José M.; Purslow, Peter P.; Gerrard, David; Hopkins, David L.; Troy, Declan; Picard, Brigitte
Abstract: Over the last two decades, proteomics have been employed to decipher the underlying factors contributing to variation in the quality of muscle foods, including beef tenderness. One such approach is the application of high-throughput protein analytical platforms in the identification of meat quality biomarkers. To broaden our understanding about the biological mechanisms underpinning meat tenderization across a large number of studies, an integromics study was performed to review the current status of protein biomarker discovery targeting beef tenderness. This meta-analysis is the first to gather and propose a comprehensive list of 124 putative protein biomarkers derived from 28 independent proteomics-based experiments, from which 33 robust candidates were identified worthy of evaluation using targeted or untargeted data-independent acquisition proteomic methods. We further provide an overview of the interconnectedness of the main biological pathways impacting tenderness determination after multistep analyses including Gene Ontology annotations, pathway and process enrichment and literature mining, and specifically discuss the major proteins and pathways most often reported in proteomics research. Graphical abstract: Unlabelled Image Highlights: Beef tenderness proteomics studies published during the last decade were gathered and analyzed. 124 protein biomarkers of beef tenderness were retrieved from 28 independent proteomics experiments. Protein biomarkers of beef tenderness belong to 6 interconnected biological pathways. 64 biomarkers were identified with a cut-off ≥2 and 33 robust biomarkers were shortlisted with a cut-off ≥4. Muscle structure, energy metabolism and cellular responses to stress and oxidative stress are the main pathways underpinning beef tenderness determination.